Intelektual Islam dan Kontribusianya atas Kemajuan Dunia Barat - Ach Syaikhu (STAIFAS-Press, 2019)
Islam is a religion that has virtue values, which are rahmatan lil'alamin. In the designation as a universal religion, namely the teachings of Islam which is intended for all people, not related to place and time. This assures us that Islam and its teachings are a basic key in constructing the social life of society. Historically, Islam has had a major role in the progress of the world, including in the West. This paper discusses the forms of Islamic intellectual contributions and their thoughts on the progress of civilization in the Western World. The author uses the method of literature study to discuss and dissect more deeply the contribution of Islamic intellectuals to the progress of the West. The results obtained are, Islam contributes greatly to the advancement of Western civilization, which when the Western world experiences the formation of thought in the development of science and civilization, at that time Islam also experienced a glory period. This is what makes Western scientists flock to explore Islam deeper and apply it back to the West.